The Effects of the National Centralized Drug Purchasing Pilot Program on Nucleos(t)ide Analogs in Shenzhen City: An Interrupted Time Series Analysis - Wen, Xiaotong; Yin, Shicheng; Cui, Lanyue; Mao, Lining; Lin, Zhaoyu; Yaermaimaiti, Zilalai; Geng, Xin; Li, Yingxia; Yang, Ying; Cui, Dan; Mao, Zongfu (Frontiers in Public Health, 2021)
Objectives: To assess the effects of the National Centralized Drug Purchasing Pilot Program on nucleos(t)ide analogs(NAs) in Shenzhen city. Methods: Drugs procurement records in medical institutions was analysed covering the period from January 2018 to December 2019. An interrupted time series analysis was used to evaluate the impact of “4+7” pilot policy on NAs in Shenzhen city. The outcome measures were usage volume, expenditures, daily cost and distribution structure of NAs. Findings: After the introduction of “4+7” pilot policy, the DDDs of NAs drugs increased 76.48%, the expenditures and DDDc of NAs decreased by 45.43%, 69.08%, respectively. The proportion of winning products in Entecavir and Tenofovir Fumarate DDDs increased 64.21% and 19.20%, respectively. The post-intervention period witnessed a significant increase in the regression level for NAs DDDs (level coefficient: β2=631.87, p<0.05). The expenditures (trend coefficient: β3=392.24, p<0.05) and DDDc (level coefficient: β2=-6.17, p<0.001; trend coefficient: β3=-0.21, p<0.05) of NAs showed decreasing trend in the post-intervention period. The expenditures of original products and generic products both showed a decreasing trend in the post-intervention period (trend coefficient: β3=-372.78, p<0.05，trend coefficient: β3=-130.78, p<0.05，respectively.) The DDDc of original products in the policy-related varieties was a significant decrease in the regression slope and level (level coefficient: β2=-2.18, p<0.05; trend coefficient: β3=-0.32, p<0.01). Conclusion: After the implementation of the "4+7" policy, the DDDc of NAs decreased, the accessibility of policy-related drugs was improved, the usage of generic medicine was promoted.